Long non-coding RNA in osteogenesis: A new world to be explored. Issue 2 (February 2019) - Zhang, J.; Hao, X.; Yin, M.; Xu, T.; Guo, F.
Abstract : Long non-coding RNAs (lncRNAs) are transcripts longer than 200 nucleotides with limited coding potential, which have emerged as novel regulators in many biological and pathological processes, including growth, development, and oncogenesis. Accumulating evidence suggests that lncRNAs have a special role in the osteogenic differentiation of various types of cell, including stem cells from different sources such as embryo, bone marrow, adipose tissue and periodontal ligaments, and induced pluripotent stem cells. Involved in complex mechanisms, lncRNAs regulate osteogenic markers and key regulators and pathways in osteogenic differentiation. In this review, we provide insights into the functions and molecular mechanisms of lncRNAs in osteogenesis and highlight their emerging roles and clinical value in regenerative medicine and osteogenesis-related diseases. Cite this article : J. Zhang, X. Hao, M. Yin, T. Xu, F. Guo. Long non-coding RNA in osteogenesis: A new world to be explored. Bone Joint Res 2019;8:73–80. DOI: 10.1302/2046-3758.82.BJR-2018-0074.R1.